EVALUASI NILAI GIZI SECARA BIOLOGI DENGAN TETRAHYMENA PYRIFORMIS GL, UNTUK BEBERAPA INTISARI JENIS KACANG·KACANGAN - T Lindajati; Yetty Mulyati I; R. H Hari (Jurnal Kimia Terapan Indonesia, 1991)
Bioassay using Tetrahymena pyriformis GL was applied to evaluate the nutritive value of soybean (Glycine max), lablab (Lablab purpureus), lamtoro sabrang (Acacia spy, orok-orok (Crotalaria sp) and turi (Sesbania grandiflora). The beans were tested either before or after being fermented with Rhizopus oligosporus Ub. Pepsin was used ill predigestion of the samples for the assay. It was found that cooked and fermented soybean, lablab and orok- orok had the relative nutritive value (RNV) approximating that of casein standard which had been set at a value of 100. Cooked lamtoro sabrang and turl had the RNV lower than that of the casein standard, i.e. 67 % and 22 % respectively before fermentation with Rhizopus oligosporus Ub. However, despite the fact that no change was found ill the RNV of lamtoro sabrang there was an improvement in the RNV of turi after fermentation, i.e from 22% t044 %.